Model Log-Linier 4 Dimensi (Studi Kasus Hubungan Antara Gender, Durasi Tidur, Ekstrakurikuler dan Hasil belajar Siswa SMAN 1 Kualuh Hulu) - Maxtulus Junedy Nababan; Gayus Simarmata (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
This study was conducted to determine the best log-linear model describing the relationship between gender, sleep duration, extracurricular activities, and student learning outcomes at SMAN 1 Kualuh Hulu. A log-linear analysis approach was used to identify interaction patterns among the variables and evaluate their contribution to student academic performance. The findings showed that the selected model adequately explained the structure of the observed data. A significant three-way interaction was identified between learning outcomes, sleep duration, and gender. The results indicated that insufficient sleep duration had a negative impact on student learning outcomes, and this effect varied by gender. Female students were found to be more vulnerable to decreased academic performance caused by sleep disturbances compared to male students. Meanwhile, extracurricular activities did not demonstrate a significant direct interaction with learning outcomes. This suggests that participation in extracurricular activities was not a major factor influencing differences in academic achievement among students at SMAN 1 Kualuh Hulu.